Pterostilbene influences glycemia and lipidemia and enhances antioxidant status in the liver of rats that consumed sucrose solution - de Morais, Juliana Maria Bitencourt; Cruz, Ellen Mayara Souza; da Rosa, Carlos Vinícius Dalto; Cesário, Roberta Carvalho [UNESP]; Comar, Jurandir Fernando; Moreira, Carolina Campos Lima; Chuffa, Luiz Gustavo de Almeida [UNESP]; Seiva, Fábio Rodrigues Ferreira (Elsevier, 2021)
Aims: The present study investigated the potential effects of pterostilbene (PT) on glycemic and lipid profiles, fat storage, cardiovascular indices, and hepatic parameters of rats fed with sucrose solution. Main methods: 24 male Wistar rats received either drinking water or a 40% sucrose solution over a period of 140 days. After this period, animals were randomly allocated into four groups (n = 6): Control (C), C + Pterostilbene (PT), Sucrose (S), and S + PT. Pterostilbene (40 mg/kg) was given orally for 45 consecutive days. Key findings: Pterostilbene did not influence morphometric and nutritional parameters. The insulin sensitivity index TyG was elevated in the C + PT group (p < 0.01) and reduced in S + PT group (p < 0.05). Basal glucose levels were lower in the S + PT group (p < 0.05), and the glycemic response was improved with PT treatment in glucose provocative tests. Conversely, rats from the C + PT group showed impaired glucose disposal during those tests. Lipid profile was partially improved by PT treatment. Hepatic oxidative stress in the S group was improved after PT treatment. In the C group, PT reduced SOD activity, glutathione levels, and increased catalase activity. Collagen content was reduced by PT treatment. Significance: PT effects depends on the type of diet the animals were submitted. In rats fed with sucrose-solution, PT confirmed its positive effects, improving glucose and lipid profile, and acting as a potent antioxidant. The effects of PT on rats that consumed a normal diet were very discrete or even undesirable. We suggest caution with indiscriminate consume of natural compounds by healthy subjects.
Keywords: Hepatic tissue; Oxidative stress; Polyphenol; Sugar-enriched beverage